2020
DOI: 10.1007/s42600-019-00032-z
|View full text |Cite
|
Sign up to set email alerts
|

An unsupervised approach to improve contrast and segmentation of blood vessels in retinal images using CLAHE, 2D Gabor wavelet, and morphological operations

Abstract: Purpose Retinopathies are the leading cause of eyesight loss, especially among diabetics. Due to the low contrast of blood vessels in fundus images, the visual inspection is a challenging job even for specialists. In this context, this work aims to implement image processing techniques to support contrast enhancement and segmentation of retinal blood vessels. Methods The initial proposal consisted only of green channel separation, contrast limited adaptive histogram equalization, and 2D Gabor wavelet and mathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Zhang et al used the Kirsch operator as the convolution kernel for matched filtering, but its segmentation detection effect in microscopic blood vessels with low contrast is still not obvious, and there are voids in the middle of the segmented detected blood vessels [14]. Rocha et al used Gabor transform to manipulate fundus images to extract pixels and regions that match the vessel features to obtain segmentation detection results, but the implementation process needs to be supplemented with a large number of presegmented standard images, and in most cases, there are insufficient conditions for implementation [15]. Joseph et al used a simple pulse-coupled neural network and a fast 2D Otsu threshold segmentation method combined with a distributed genetic algorithm to extract the main blood vessels and proposed a method to automatically detect the retinal blood vessels in the fundus [16].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al used the Kirsch operator as the convolution kernel for matched filtering, but its segmentation detection effect in microscopic blood vessels with low contrast is still not obvious, and there are voids in the middle of the segmented detected blood vessels [14]. Rocha et al used Gabor transform to manipulate fundus images to extract pixels and regions that match the vessel features to obtain segmentation detection results, but the implementation process needs to be supplemented with a large number of presegmented standard images, and in most cases, there are insufficient conditions for implementation [15]. Joseph et al used a simple pulse-coupled neural network and a fast 2D Otsu threshold segmentation method combined with a distributed genetic algorithm to extract the main blood vessels and proposed a method to automatically detect the retinal blood vessels in the fundus [16].…”
Section: Introductionmentioning
confidence: 99%
“…CLAHE technique is used to increase image contrast by providing a limit value (clip limit) so that the image looks clearer [23]. The contrast value given must be limited so that there is no excessive contrast increase in the histogram [24]. To calculate the clip limit of a histogram using Formula (2).…”
Section: B Pre-processingmentioning
confidence: 99%
“…According to Marin et al [66] experiments, the method suggested by Ricci et The main issue with supervised methods is their dependency on robust feature extraction to classify the pixels of the image into vessels and background. Since this feature vector must be calculated for each pixel, the algorithms become almost complicated, and the procedure will be time-consuming due to the training stage [47,48,68].…”
Section: Supervised Methodsmentioning
confidence: 99%
“…Da Rocha et al [48] performed pre-processing on the green channel of the RGB images from the DRIVE database by creating the complement of the image and making a mask of the region of interest (ROI) of the retina area, followed by an adaptive method of histogram equalization. The next step consists of 2D Gabor Wavelet Transform (GWT) and closing operation.…”
Section: Unsupervised Rule-based Methodsmentioning
confidence: 99%
See 1 more Smart Citation